2015
DOI: 10.1104/pp.114.253682
|View full text |Cite
|
Sign up to set email alerts
|

A Heteromeric Membrane-Bound Prenyltransferase Complex from Hop Catalyzes Three Sequential Aromatic Prenylations in the Bitter Acid Pathway

Abstract: Bitter acids (a and b types) account for more than 30% of the fresh weight of hop (Humulus lupulus) glandular trichomes and are well known for their contribution to the bitter taste of beer. These multiprenylated chemicals also show diverse biological activities, some of which have potential benefits to human health. The bitter acid biosynthetic pathway has been investigated extensively, and the genes for the early steps of bitter acid synthesis have been cloned and functionally characterized. However, little … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
107
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(111 citation statements)
references
References 42 publications
2
107
1
1
Order By: Relevance
“…Because some plastid-localized PTs partially or completely failed to be functionally expressed in yeast with the transit peptide (Akashi et al 2009, Shen et al 2012, Munakata et al 2014, Li et al 2015), the CDSs of the N-terminal-truncated forms without putative transit peptides were also PCR-amplified and introduced into yeast expression vectors. Subsequently, 10 constructs, namely the native CDSs of PT3, PT4, PT5, PT6 and PT7 and their truncated forms ΔTP-PT3, ΔTP-PT4, ΔTP-PT5, ΔTP-PT6 and ΔTP-PT7, respectively, were expressed in yeast.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because some plastid-localized PTs partially or completely failed to be functionally expressed in yeast with the transit peptide (Akashi et al 2009, Shen et al 2012, Munakata et al 2014, Li et al 2015), the CDSs of the N-terminal-truncated forms without putative transit peptides were also PCR-amplified and introduced into yeast expression vectors. Subsequently, 10 constructs, namely the native CDSs of PT3, PT4, PT5, PT6 and PT7 and their truncated forms ΔTP-PT3, ΔTP-PT4, ΔTP-PT5, ΔTP-PT6 and ΔTP-PT7, respectively, were expressed in yeast.…”
Section: Resultsmentioning
confidence: 99%
“…Prenylation of flavonoids is catalyzed by prenyltransferases (PTs), which transfer prenyl moieties from allylic prenyl diphosphate to flavonoid skeletons. The flavonoid-specific PT naringenin 8-dimethylallyltransferase (SfN8DT) was initially identified in the leguminous plant Sophora flavescens (Sasaki et al 2008), and several plant PTs that act on flavonoids and other aromatic compounds have been molecularly and biochemically characterized (Akashi et al 2009, Sasaki et al 2011, Shen et al 2012, Chen et al 2013, Karamat et al 2014, Li et al 2014, Munakata et al 2014, Wang et al 2014, Li et al 2015, Munakata et al 2016). A recent report on hop PTs demonstrated that a complex of two PTs, as a metabolon, catalyzes three steps of sequential aromatic prenylation in β-bitter acid biosynthesis (Li et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Of these software packages, citations have been found for JCat and OPTIMIZER for expression systems such as E. coli (Fahimi et al 2016;Guo et al 2016;Karkhah & Amani 2016;Zhao et al 2016), S. cerevisiae (Ask et al 2013;Guadalupe-Medina et al 2013;Li et al 2015;Milne et al 2015;Solis-Escalante et al 2013), N. benthamiana (Binder et al 2014), HEK293 cells (Shah et al 2015), B. subtilis (Reilman et al 2014), C. crescentus (Ko et al 2013), P. putida (Dammeyer et al 2013;Dammeyer et al 2011), S.…”
Section: Acc E P Ted P R E P R I Ntmentioning
confidence: 99%
“…Examples include bitter acids in hops, which give flavor to beers [85], and phytoalexins, which appear in both legumes [86] and Sophora flavescens [87]. In bacteria, aurachins are potent inhibitors of the respiration chain [88].…”
Section: Other Ubia Superfamily Membersmentioning
confidence: 99%